La competencia estatal en materia de becas y ayudas al estudio: fundamento y alcance - Canal Muñoz, José (Revista de Derecho Político, 2018)
Resumen: Las becas y ayudas al estudio vienen siendo calificadas en el ordenamiento español como subvenciones públicas. Este trabajo sostiene que sería más adecuado con nuestro marco constitucional otorgarles la consideración de prestaciones públicas, financiadas con cargo a los Presupuestos Generales del Estado. La revisión de la naturaleza jurídica de las becas y ayudas al estudio tendría relevantes consecuencias: por un lado, recomendaría que el Legislador definiese el contenido del derecho a obtener estas prestaciones públicas, de forma similar a otros ámbitos de la actuación administrativa. Por otra parte, permitiría fundamentar la revisión de la doctrina del Tribunal Constitucional sobre el reparto de las competencias entre el Estado y las Comunidades Autónomas en esta materia, a partir de la invocación de la regla 1.ª del artículo 149.1 CE. Summary: 1. Public funding of education. 2. The right to obtain grants. 2.1. Constitutional or legal nature of the right. 2.2. Content and constitutional limits of the right. 3. The student grants system. 3.1. Concept, characteristics of student grants. 3.2. Nature of student grants. 4. The territorial distribution of competences related to grants. 4.1. Regulatory power. 4.2. Executive powers. 5. A possible revision of basis and scope of competence. 5.1. Grants as public service. 5.2. The rule 1 of article 149.1 of the Constitution. 6. Conclusions. Abstract: Scholarships are classified in the Spanish legal system as public subsidies. This paper argues that it would be more appropriate with our constitutional framework to confer them the consideration of public benefits, financed by Publics Budgets. The review of the legal nature of student grants would have important consequences: on the one hand, Law should rule the content of the right to obtain these public benefits, in a similar way to other areas of Administration. On the other hand, the Constitutional Court may review its position on the distribution of the competences between the State and the Autonomous Regions, by calling the rule 1 of article 149.1 of the Constitution.